2018
DOI: 10.1038/s41386-018-0256-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiologic measures of target engagement predict response to auditory-based cognitive training in treatment refractory schizophrenia

Abstract: Cognitive impairment is a core feature of schizophrenia and a strong predictor of psychosocial disability. Auditory-based targeted cognitive training (TCT) aims to enhance verbal learning and other domains of cognitive functioning through "bottom-up" tuning of the neural systems underlying early auditory information processing (EAIP). Although TCT has demonstrated efficacy at the group level, individual response to TCT varies considerably, with nearly half of patients showing little-to-no benefit. EEG measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 61 publications
2
35
0
Order By: Relevance
“…Cognitive training must address limitations in perceptual/pre-attentive processing first (for a review, (Vinogradov et al, 2012)). This hope was preliminarily bolstered by some finding of learning-induced neuroplasticity, in which training in early auditory or visual processes results in substantial gains in verbal or visual cognitive processes through "bottom-up" tuning of the neural systems (Adcock et al, 2009;Biagianti et al, 2016;Dale et al, 2016;Fisher et al, 2009;Hochberger et al, 2019;Surti et al, 2011).…”
Section: Implications For Future Treatment Studiesmentioning
confidence: 99%
“…Cognitive training must address limitations in perceptual/pre-attentive processing first (for a review, (Vinogradov et al, 2012)). This hope was preliminarily bolstered by some finding of learning-induced neuroplasticity, in which training in early auditory or visual processes results in substantial gains in verbal or visual cognitive processes through "bottom-up" tuning of the neural systems (Adcock et al, 2009;Biagianti et al, 2016;Dale et al, 2016;Fisher et al, 2009;Hochberger et al, 2019;Surti et al, 2011).…”
Section: Implications For Future Treatment Studiesmentioning
confidence: 99%
“…RON is thought to reflect a reorienting of attention back to the foreground task, though the underlying psychological construct is less developed. Important for the current study, the ADR complex has been shown to be sensitive to a number of CNS perturbations including acute pharmacologic challenges and cognitive training interventions (16)(17)(18)(19)(20)(21)(22). The ADR components are translational biomarkers elicited in the absence of directed attention and index functionally relevant networks, thus they are increasingly used as biomarkers in the development of interventions that target CNS dysfunction (17,21,(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…This sensory prediction error response has also been shown to relate to functional ability in people at risk for schizophrenia [8]. There are pilot studies indicating it may be able to predict and be an objective indicator of people who would benefit from psychosocial interventions [9][10][11]. Being able to have more precise information on who would respond to interventions, especially psychosocial interventions that require a weekly commitment over months, would benefit participants and not expose people to the potentially demoralising effect of attending a therapy that they were not able to benefit from [12].…”
Section: Background and Rationalementioning
confidence: 99%